Analysis of the curative effect of limb salvage therapy in patients with soft tissue sarcoma who underwent extensive resection combined with skin flap transplantation - Wu, Wei-na; Cao, Hai-ying; Feng, Zhen (Nepalese Journal of Cancer, 2021)
Purpose: Patients who were diagnosed with soft tissue sarcoma (STS) of limbs and met the indications for amputation because of no effective soft tissue coverage after extensive tumor resection were treated with skin flap transplantation and therapeutic courses were observed. Methods: A total of 23 patients, pathologically diagnosed as soft tissue sarcoma from January 2011 to June 2015 and whose effective soft tissue coverage was not guaranteed due to extensive tumor resections were included. They underwent extensive tumor excision and skin flap grafting. The postoperative follow-up, tumor control and functional recovery was evaluated as per the Musculoskeletal Tumor Society (MSTS) score. Results: The follow-up time was from 8 to 60 months, with an average follow-up of 39.69 months. Of the 23 patients, 10(43.47%) died of tumor metastasis from 8th to 23rd months after surgery. In these 10 cases, 2 cases (8.70%) subsequently underwent amputation because of local tumor recurrence. The remaining 13 patients are recurrence free till date of follow up. The MSTS limb function score at 3 months after surgery of all patients were 7-28 points, with an average of 22.56 points, and the excellent and fair scores are observed in 91.30% of patients. Conclusion: For patients who cannot achieve effective soft tissue coverage after extensive resection of soft tissue sarcoma and meet the indications of amputation can have limb preservation by extensive tumor resection combined with skin flap transplantation with a good functional results